'Pedestrian falls' as necessary addition to the current definition of traffic crashes for improved public health policies. (September 2017) - Methorst, Rob; Schepers, Paul; Christie, Nicola; Dijst, Martin; Risser, Ralf; Sauter, Daniel; van Wee, Bert
Highlights: The current definition of road crashes neglects pedestrian falls 4–9 times as many pedestrians are injured in falls than in pedestrian-vehicle collisions Exclusion leads to biased conclusions for transport and safety policies Mobility of the elderly and public health interests are not adequately served Discussion about updating the road crash definition is recommended